Water quality in Costa Rica - Hidalgo León, Hugo G. (2019)
This book provides an overview of surface and groundwater quality and impacts on human consumption, agriculture and ecosystem services in each country, thereby creating a hemisphere-wide picture of the current status and future challenges for the quality of essential water resources.